Efecto sobre la microbiota bacteriana intestinal de una fracción de fructooligosacáridos de la raíz de Psacalium decompositum - Juárez Pérez, María Guadalupe (Universidad Autónoma Metropolitana, 2020)
Psacalium decompositum is a shrub that grows in northern Mexico and the southwestern of United States. A decoction with water of the root of this species is used by healers Tarahumaras, Yaquis and Pimas as a traditional remedy to relieve pain and as an alternative treatment for diseases. Experimentally, a fraction of fructooligosaccharides (FOS) obtained from this species has been shown to have hypoglycemic and anti-inflammatory effects. Therefore, the objective of this study was to evaluate the effect of FOS on the gut microbiota in a model with healthy rats, arranged in 1) a control group, 2) a prebiotic control group and 3) an experimental group FOS. The treatments were administered daily intragastric route for 15 days. The feces were collected at the beginning and end of the study for a microbiological (in selective and differential and non-selective culture media) and metagenomic analysis (region V3-V4 of the 16S rRNA gene). Sequence processing and analysis was performed with the Geneious V11 software and with scripts in QIIME environment. In the microbiological analysis, no statistically significant effect was found after administration of the FOS fraction on pathogenic microorganisms. The taxonomic assignment shows that the predominant phyla in the intestinal microbiota corresponds to Firmicutes, Bacteroidetes and Proteobacteria. In addition, in the FOS group treatment the abundance found of beneficial genera such as Bifidobacterium, Lactobacillus and butyrate-producing microbial genera, is greater with respect to the control groups. The results suggest that the fraction has an effect like as to reported for chicory inulin, that has a prebiotic effect. This study shown that the FOS fraction of P. decompositum improves the abundance of microbial genera considered beneficial in the gut microbiota of healthy rats. The effect may be mediated by shortchain fatty acids production, mainly butyrate, and also with the growth of microorganisms that help maintain gut homeostasis. ; Psacalium decompositum es un arbusto que crece en el norte de México y en el suroeste de Estados Unidos. Una decocción con agua de la raíz de esta especie es utilizada por curanderos Tarahumaras, Yaquis y Pimas como remedio tradicional para aliviar dolores y como tratamiento alternativo de enfermedades. Una fracción de fructooligosacáridos (FOS) obtenida de esta especie mostró efectos hipoglucémico y antiinflamatorio a nivel experimental. El objetivo del presente trabajo fue evaluar el efecto de esta fracción sobre la microbiota bacteriana intestinal en ratas sanas. Se formaron tres grupos experimentales: 1) grupo control, 2) grupo control prebiótico y 3) grupo experimental FOS. Los tratamientos fueron administrados diariamente, por vía intragástrica, durante 15 días. Se colectaron las heces al inicio y término del estudio, para realizar un análisis microbiológico (en medios selectivos y diferenciales y no selectivos) y metagenómico (región V3-V4 del gen ARNr 16S). El procesamiento y análisis de secuencias se realizó con el software Geneious V11 y con scripts en ambiente QIIME. De acuerdo con el análisis microbiológico, no se encontró efecto estadísticamente significativo en la composición de microorganismos patógenos tras la administración de la fracción de FOS. La asignación taxonómica mostró que los phyla predominantes en la microbiota intestinal son Firmicutes, Bacteroidetes y Proteobacteria. Además, en el grupo tratado con FOS la abundancia encontrada de géneros benéficos como Bifidobacterium, Lactobacillus y microbiota productora de butirato fue mayor con respecto a los grupos control. Los resultados sugieren que la fracción tiene un efecto parecido al reportado para la inulina de achicoria, la cual presenta efecto prebiótico. Este estudio demuestra que la fracción de FOS de P. decompositum mejora la abundancia de géneros microbianos considerados como benéficos en la microbiota intestinal de ratas sanas. El efecto puede estar mediado por la producción de ácidos grasos de cadena corta, principalmente butirato, y también por el crecimiento de microorganismos que ayudan a mantener la homeostasis intestinal.